Letramento funcional em saúde para manutenção do envelhecimento ativo e fortalecimento do autocuidado em pessoa idosa - Conceição, Krycia Renata da Rocha (2024)
The aging process is a natural phenomenon that occurs in all human beings. One technique that can be used in healthy aging programs is Functional Health Literacy (LFS). LFS is the ability to read, understand and practice health-related guidance. The objective of this research was to develop and apply LFS techniques, through health education workshops to promote self-care and improve the perception of quality of life in a group of elderly people. This is a descriptive study with a quantitative approach. It was carried out in 2024 with people aged between 60-90 years of both sexes in the city of Conceição do Araguaia-Pará-Brazil. An instrument was applied to identify socioeconomic profiles - Critério Brasil, from the Brazilian Association of Business and Research (ABEP).The instrument culturally adapted and validated in Brazil to assess the level of functional literacy was the Test of Functional Health Literacy in Adults (B- TOFHLA) and to assess quality of life, the World Health Organization Quality of Life Assessment instruments were used ( Whoqol-Bref) and for quality of life in the elderly - WHOQOL – OLD, both developed by the World Health Organization (WHO). The ASA-A scale was used to assess Self-Care Capabilities (ASA-A). 41 elderly people participated in the study. The overall average age was 67.7 (6.7) years. The group characterization results highlight that the majority were women, married, illiterate or with incomplete primary education, users of the Unified Health System (SUS) and from the most vulnerable economic strata. In relation to the perception of quality of life, it is possible to observe higher scores in the psychological and social relationships domains. The lowest scores appeared in the physical and environmental domains. According to the WHOQOL-Old test applied at the beginning of the research and post-intervention, we observed that all domains changed in a statistically significant way. The research showed that the interventions helped with the LFS of some participants and improved the self-care capacity observed at the beginning of the research. Based on the application of the ASA-A instrument, it was possible to notice that the participants' self-care capacity was already excellent (above 100) and became even better. When we compared the pre- and post- intervention LFS scores, no statistical differences were observed. The findings of this research identified that LFS strategies through health education workshops on self-care for elderly people obtained positive results, improving the participants' conception of their own self-care and contributing to improving their perception of their quality of life. These results confirm the relevance of proposing educational actions focused on these themes with an emphasis on active and healthy aging using functional health literacy strategies.